The Supernatural as a Feminist Tool in Elizabeth Stuart Phelps's Writings. - Narbona-Carrión, María Dolores (My University, 2024)
Elizabeth Stuart Phelps (1844-1911) is a writer who became extremely famous in the past, was later relegated to a very secondary and “non-canonical” position. She has traditionally been considered as a writer of sentimental or domestic fiction, of religious literature, as a social reformer and as a feminist. However, her contributions to the supernatural subgenre have not been sufficiently recognised and studied. Consequently, this paper focuses on their analysis and highlights how one of the reasons for their oblivion might be precisely that they are strongly related to some of the labels and interests of Phelps previously mentioned. In effect, a thorough study of Phelps’s works demonstrates that, for her, it was impossible to separate literature from reality, even when she wrote about such abstract subjects as the otherworldly. This was based on her conviction that professional writers had the moral duty of portraying social illnesses with the intention of ameliorating the life of the suffering, especially of women. Therefore, the main objective of this essay is to bring to light Phelps’s literary works dealing with the supernatural principally with the intention of revealing her wish to use them as a metaphorical means to denounce the unjust situation of those represented by her characters, especially of women. Thus, the methodology underpinning this study is mainly historiographical, sociological, biographical, and feminist, as it focuses on the reflection of Phelps’s 19th-century US context, her own life and that of other women. This theoretical framework facilitates the analysis of concrete Phelps’s literary works dealing with the supernatural, with the intention of revealing the author’s effort to portray and ameliorate the oppressive situation of many of her contemporary women. Finally, we will recognise Phelps’s bravery, because, with this type of writings, she was challenging her conservative religious and literary context. M. D. Narbona Carrión.
Keywords: Literatura norteamericana - Autoras - Historia y crítica; Feminismo - S. XIX; 19th-century women’s American literature; Gothic literature; Elizabeth Stuart Phelps; Supernatural literature; Feminist literature